2022
DOI: 10.7759/cureus.22975
|View full text |Cite
|
Sign up to set email alerts
|

Chilaiditi Syndrome Presenting as Partial Colonic Obstruction

Abstract: Chilaiditi sign is a rare incidental radiographic finding where bowel is interposed between the diaphragm and the liver, often seen as air under the right hemidiaphragm. A majority of patients with Chilaiditi sign are asymptomatic and remain so throughout their lifetime. Chilaiditi sign is recategorized as Chilaiditi syndrome if it becomes symptomatic and is a very rare etiology of bowel obstruction. As bowel obstruction confers a huge financial burden to the health care system, studies of even the rarer etiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…However, a second radiograph with positional alterations should show air movement if air has instead accumulated in the peritoneal cavity. CT can be used to confirm anything in question [ 4 ]. Similarly, for the situation we presented in this report, abdominal CT showed that there was a colon interposition between the liver and the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…However, a second radiograph with positional alterations should show air movement if air has instead accumulated in the peritoneal cavity. CT can be used to confirm anything in question [ 4 ]. Similarly, for the situation we presented in this report, abdominal CT showed that there was a colon interposition between the liver and the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…1 This can often be misinterpreted as pneumoperitoneum and subsequently lead to unwarranted emergent surgical interventions. Management of CS rests largely on conservative measures including intravenous hydration, bowel decompression, and cleansing 2 , 3 while surgery is reserved for refractory/recurrent or complicated cases. Potential complications include intestinal obstruction, bowel perforation or ischemia, colonic volvulus, and subphrenic appendicitis.…”
Section: Case Reportmentioning
confidence: 99%
“…Chilaiditi syndrome also is an unusual condition characterized by colon interposition and many factors including congenital malposition, functional disease, and intra‐abdominal procedures may contribute in development of this syndrome 7 . Both ACS and Chilaiditi syndrome are rare causes of obstruction with unknown etiology 2,8 . Since ACS has a mortality rate of 50% and clinical diagnosis is mostly delayed, having high clinical suspicion and awareness of disease manifestations is needed for improving outcomes 9 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Both ACS and Chilaiditi syndrome are rare causes of obstruction with unknown etiology. 2 , 8 Since ACS has a mortality rate of 50% and clinical diagnosis is mostly delayed, having high clinical suspicion and awareness of disease manifestations is needed for improving outcomes. 9 Herein we report the clinical course of an uncommon idiopathic ACS associated with Chilaiditi syndrome presented with obstruction.…”
Section: Introductionmentioning
confidence: 99%